THE EDUCATION SYSTEM IN THE MADRASAHS OF THE BUKHARA EMIRATE: ACHIEVEMENTS AND SHORTCOMINGS - Nigora, Elmurodova (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to examine the educational system of madrasas in the Bukhara Emirate by analyzing their contributions to religious and secular education, their socio-cultural influence, and their role in the formation of the scientific environment. Method: Utilizing a historical methodology, supported by source analysis and comparative analysis, the research investigates the institutional and pedagogical characteristics of madrasas from the late 19th to early 20th centuries. Results: The findings reveal that madrasas were central to the cultural and educational life of the Bukhara Emirate, serving both Islamic teachings and state ideology. Despite a strong tradition of religious scholarship, the system faced significant limitations, including outdated curricula and limited emphasis on applied sciences, which ultimately hindered broader scientific and societal progress. These shortcomings catalyzed the emergence of reform efforts in the madrasa system during the specified period. Novelty: This article offers a systematic classification of the strengths and weaknesses of the madrasa education system in the Bukhara Emirate and presents an original historical interpretation of the factors that necessitated educational reform, contributing to the broader discourse on Islamic education and modernization